Prevalence of Patients with Comorbidities at the Undergraduate Clinic of Piracicaba Dental School – Brazil - Mazzo, Beatriz; dos Santos, Victor Augusto Benedicto; Figueroba, Sidney; Soares, Adriana de Jesus; Henriques, Guilherme Elias Pessanha; Barbin, Thomas; Groppo, Francisco Carlos (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Objectives: The aim of this study was to evaluate the prevalence of comorbidities in patients treated at the FOP-UNICAMP undergraduate clinic. A survey based on patient records obtained between June 2021 and November 2022 was conducted. Comorbidities, such as hypertension, diabetes, and heart diseases, among others, were identified. Additionally, dental history, gender, and age were assessed. Methods: The data were analyzed using chi-square and Mann-Whitney tests. A total of 2.857 medical records were included in the study. Results: There were no significant differences (p=0.12) in the ages (median; 1st and 3rd quartiles) between females (49.6; 36.3 - 60.1 years) and males (50.4; 35 - 62.5 years). However, there was a significantly higher number of females (n=1716) compared to males (n=1141) (p<0.0001), and the majority of patients fell into the 35-65 years age group (n=1676). There was a higher proportion of females under medical treatment or with comorbidities, and these patients were older compared to others (p<0.0001). There were no significant differences (p>0.05) between genders in relation to cardiovascular diseases (M=116; F=170), hypertension (M=320; F=510), diabetes (M=153; F=225), or the combination of these diseases. Hypertension was the most prevalent condition (29.1%). The patients with these diseases were older (p<0.0001) compared to those without these conditions. Depression and/or anxiety were more common in females and older patients. Conclusions: In conclusion, there was a higher proportion of comorbidities in females, and age was higher in individuals with comorbidities.